1991
DOI: 10.1002/ptr.2650050408
|View full text |Cite
|
Sign up to set email alerts
|

Choleretic action of andrographolide obtained from Andrographis paniculata in rats

Abstract: Andrographolide, a diterpene, isolated from Androgruphis puniculala exhibited a strong choleratic action when administered intraperitoneally (i.p.) to albino rats. This substance induced an increase in bile flow together with a change in the physical properties of the bile secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Andrographolide, a diterpene lactone (see structure) isolated from Andrographis paniculata (Acanthaceae), has been shown to possess hepatoprotective activity against hepatotoxins including carbon tetrachloride (Handa and Sharma, 1990a;Kapil et al, 1993), galactosamine and paracetamol (Handa and Sharma, 1990b;Visen et al, 1993) and ethanol (Pramyothin et al, 1994). Andrographolide has also been shown to have antidiarrhoeal (Gupta et al, 1990), choleretic (Tripathi and Tripathi, 1991;Shukla et al, 1992) and analgesic, antipyretic and antiulcerogenic effects (Madav et al, 1995). Madav et al (1996) have recently reported the in vivo antiinflammatory activity of andrographolide.…”
Section: Introductionmentioning
confidence: 99%
“…Andrographolide, a diterpene lactone (see structure) isolated from Andrographis paniculata (Acanthaceae), has been shown to possess hepatoprotective activity against hepatotoxins including carbon tetrachloride (Handa and Sharma, 1990a;Kapil et al, 1993), galactosamine and paracetamol (Handa and Sharma, 1990b;Visen et al, 1993) and ethanol (Pramyothin et al, 1994). Andrographolide has also been shown to have antidiarrhoeal (Gupta et al, 1990), choleretic (Tripathi and Tripathi, 1991;Shukla et al, 1992) and analgesic, antipyretic and antiulcerogenic effects (Madav et al, 1995). Madav et al (1996) have recently reported the in vivo antiinflammatory activity of andrographolide.…”
Section: Introductionmentioning
confidence: 99%